2016
DOI: 10.1038/mi.2015.89
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of NLRP3 inflammasome activation and its role in NSAID-induced enteropathy

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) induce cytokines, including tumor necrosis factor-α and interleukins (ILs), in the small intestine via a Toll-like receptor 4 (TLR4)-dependent pathway, leading to intestinal ulceration. Activation of the inflammasome promotes pro-caspase-1 cleavage, leading to pro-IL-1β maturation. We examined the role of NLRP3 inflammasome in NSAID-induced enteropathy. Small intestinal damage developed 3 h after indomethacin administration, accompanied by increases in IL-1β and NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 42 publications
6
41
0
Order By: Relevance
“…Our previous study revealed inflammasome activation in inflammatory cells, including macrophages, during the development of NSAID-induced small intestinal damage [7]. In addition, it has been reported that isoliquiritigenin is rapidly metabolized and only a small amount is retained in the small intestine [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study revealed inflammasome activation in inflammatory cells, including macrophages, during the development of NSAID-induced small intestinal damage [7]. In addition, it has been reported that isoliquiritigenin is rapidly metabolized and only a small amount is retained in the small intestine [17].…”
Section: Discussionmentioning
confidence: 99%
“…This signal promotes inflammasome assembly, leading to pro-caspase-1 and pro-IL-1β maturation [14]. We previously demonstrated that the lipopolysaccharide/TLR-4 axis mediated the first signal and the ATP/P2X 7 receptor axis mediated the second signal in NSAID-induced enteropathy [7]. Previous in vitro studies have demonstrated that isoliquiritigenin prevents TLR-4-mediated nuclear factor-κB activation by inhibiting homodimerization of TLR-4 [15], in addition to attenuating ASC oligomerization [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations